TARGETED PEDAGOGICAL SYSTEM OF DEVELOPING TOLERANCE SKILLS IN PRIMARY CLASS STUDENTS DURING THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2024)
In this article, the purposeful pedagogical system of developing tolerance skills in elementary school students is studied and highlighted. It has been studied that it is a pedagogical system aimed at developing tolerance in the whole world by forming the skills of tolerance, tolerance, endurance and worldview of accepting others.